Two new species of the genus Lathrobium (Coleoptera: Staphylinidae: Paederinae) from Gotô Islands, Japan - Sato, Yuya (Zootaxa, 2023)
Lathrobium gotoianum Y. Sato sp. nov. and Lathrobium fukuense Y. Sato sp. nov. are described from Gotô Islands, north of Kyushu, Japan. The previous record of Lathrobium pollens Sharp, 1889 in Gotô Island (Imasaka et al. 1994) may be the result of misidentification of Lathrobium gotoianum Y. Sato sp. nov.